Empowering Nurses: The Influence of Work-Life Balance, Work Ethic, and Organizational Commitment on Nurse Performance - Rarasingtyas, Listyorini; Suyono, Joko; Sari, Yunita; Azizah, Queen; Elisabeth, Damarsari Ratnasahara (Universitas Muhammadiyah Gresik, 2025)
The aim of this research is to analyze the influence of work-life balance, work ethics and organizational commitment on nurses’ performance of dr Mohamad Soewandie Hospital in Surabaya. The sample in this study was 84 nurses of dr. Mohamad Soewandie Hospital in Surabaya. The data collection technique uses a questionnaire, while the data analysis technique uses multiple linear regression. The research results prove that work-life balance, work ethics and organizational commitment have a partial and simultaneous influence on nurses performance of dr. Mohamad Soewandie Hospital in Surabaya. Among these three variables, organizational commitment is proven to have a dominant influence on nurses performance of dr Mohamad Soewandie Hospital in Surabaya.